Taboo - Rickel, Boyer (The University of Wisconsin Press, 1999)
An impressionistic memoir offers images of a life in progress, including scenes from Boyer Rickel's rural Tempe, Arizona, childhood in the 1950s; his relationship with a physically shrinking father; his eccentric teenage friendships; his growing awareness of his sexuality among young, Hispanic gays; and a trip through Italy with his lover. A personal book, but also wholly universal, Taboo investigates the way one breaks through taboos and becomes a self-realized adult.